L’interferometria SAR satellitare per la misura delle deformazioni superficiali - Chini, Marco; Bignami, Chrstian; Stramondo, Salvatore (GEOmedia, 2012)
La tecnica interferometrica, basata sull'elaborazione coerente della fase del ritorno del segnale radar dalla superficie terrestre, ha reso il telerilevamento radar uno strumento di analisi quantitativa in molteplici campi applicativi quali cartografia, geodesia, rischio sismico, idrogeologico e vulcanico. In particolare, l'InSAR consente di produrre mappe di spostamento co-sismico, ovvero di misurare il campo di deformazione superficiale causato da un terremoto con accuratezze centimetriche. Satellite SAR interferometry for the measurement of surface deformation The SAR Interferometry (InSAR) technique is mostly used to measure the characteristics of the topography and its changes during time. The interferometric technique, based on the coherent elaboration of radar returns from the surface, has made the radar remote sensing a valuable tool for a quantitative analysis in many applicative fields such as cartography, geodesy, seismic, hydrogeologic and volcanic hazards. In particular, InSAR technique is able to measure the co-seismic surface deformation caused by an earthquake with accuracies at order of centimeters. This kind of data is extremely important for the estima-tion of the geometric parameters of the seismic source which is a relevant information for the management of event scenarios.In the last decade a new technique for the elaboration of the interferometric signal arises, the multitemporal SAR Interferometry. Thanks to the exploita-tion of a conspicuous number of SAR images, it is possible detecting and monitoring the slow soil deformation with millimetric accuracies. Moreover, the recent very high resolution satellite SAR sensors make possible to apply this technique in urban areas in order to monitor single structures such as bridges, buildings, roads and so on.